Design and implementation of a BDS precise point positioning service. Issue 4 (9th October 2020) - Liu, Cheng; Gao, Weiguang; Liu, Tianxiong; Wang, Dun; Yao, Zheng; Gao, Yang; Nie, Xin; Wang, Wei; Li, Dongjun; Zhang, Weixing; Wang, Dongxia; Rao, Yongnan
Abstract: Precise point positioning (PPP) service is of great significance for BDS. The design and implementation of the service are presented. The PPP‐B2b signal of the service is constructed, which is efficient multiplexed with other signal components, and achieves compatibility between two service phases. A customized message format that can augment all visible satellites of four core constellations in mainland China is proposed. The high‐gain, 64‐ary, low‐density parity check (LDPC) coding is used, which facilitates the integrated design of the receivers. A signal quality test has revealed that the S‐curve bias (SCB) of PPP‐B2b does not exceed 0.0165 ns and the coherence between the code and the carrier of the signal is only 0.137 ∘ . A performance evaluation has indicated that at its current stage, the positioning accuracy in the horizontal and vertical directions is better than 0.15 m and 0.3 m, respectively, and the convergence time does not exceed 800 s.